COUNTDOWN TO YESTERDAY - Marr, Shirley (London : Usborne Publishing Limited, 2024)
James is stuck in the present... and that's the last place he wants to be. His parents have separated, and he must get used to living two different lives. Now, he has two homes, two bedrooms and two routes to school with nothing adding up to the one great life he used to have. James wishes he could go back to the past, to his Top Six best memories with Mum and Dad. Then, James meets Yan, a girl who looks at the world differently, and he discovers that travelling back in time might be possible. But are his memories as perfect as he remembers?
Keywords: Children of separated parents -- Juvenile fiction; Time travel -- Juvenile fiction; Friendship -- Juvenile fiction; Children's stories; Time-travel fiction